2013
DOI: 10.1111/liv.12193
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemical structures and the 1331T>C bile salt export pump polymorphism in idiosyncratic drug‐induced liver injury

Abstract: Patients carrying the C allele in the ABCB11 1331T>C polymorphism are at increased risk of developing hepatocellular type of DILI, when taking drugs containing a carbocyclic system with aromatic rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
3
31
0
1
Order By: Relevance
“…Similar differences were observed in studies of ICP [n = 491, 67% of patients versus 54% of controls, P , 0.001 (Dixon et al, 2009); n = 42, 76% of patients versus 51% of controls, P = 0.0007 (Meier et al, 2008)]. A Spanish study reported that the C-allele was associated with an increased risk of developing DILI; however, this association was observed only among those with hepatocellular liver injury (Ulzurrun et al, 2013). Recently, Dixon et al (2014) demonstrated through a conditional analysis that rs3815676 and rs7577650, rather than rs2287622 (1331T.C), associated significantly with ICP in western Europeans.…”
Section: Discussionsupporting
confidence: 53%
“…Similar differences were observed in studies of ICP [n = 491, 67% of patients versus 54% of controls, P , 0.001 (Dixon et al, 2009); n = 42, 76% of patients versus 51% of controls, P = 0.0007 (Meier et al, 2008)]. A Spanish study reported that the C-allele was associated with an increased risk of developing DILI; however, this association was observed only among those with hepatocellular liver injury (Ulzurrun et al, 2013). Recently, Dixon et al (2014) demonstrated through a conditional analysis that rs3815676 and rs7577650, rather than rs2287622 (1331T.C), associated significantly with ICP in western Europeans.…”
Section: Discussionsupporting
confidence: 53%
“…Specifically, focus has shifted to BSEP inhibition as a cause of drug-induced cholestasis (DIC) and possibly drug-induced liver injury (DILI) (Stepan et al, 2011;Kubitz et al, 2012;Bjornsson and Jonasson, 2013;Yang et al, 2013). Interest in BSEP (ABC11) has been fueled also by reports that subjects carrying certain loss-of-function/expression ABC11 alleles are predisposed to DILI (Ulzurrun et al, 2013). As a result, a considerable amount of effort has been made to set up high-throughput in vitro inhibition screens in an attempt to mitigate drug interactions involving BSEP inhibition and DIC (Morgan et al, 2010;Dawson et al, 2012;Warner et al, 2012;Pedersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing awareness that the current experimental animal models are not predictive for the human clinical situation. This discrepancy can be due to species differences in bile acid pool composition (García-Cañaveras et al, 2012;Setchell et al, 1997), in individual bile acid concentrations and in abundance and functionality of the transporters and enzymes involved in bile acid handling, as well as in their susceptibility for interference by the drug (Ulzurrun et al, 2013). Moreover, the animals used for drug testing are genetically more uniform than the human patient population and this can result in skewed results.…”
Section: Introductionmentioning
confidence: 97%
“…As prototypical BSEP inhibiting drugs we used glibenclamide and cyclosporin A. Both drugs have been associated with cholestatic DILI and are inhibitors of BSEP (Byrne et al, 2002;Goodman et al, 1987;Morgan et al, 2010;van Basten et al, 1992;Varma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%